Potentially inappropriate medications based on TIME criteria and risk of in-hospital mortality in COVID-19 patients - KOCAKAYA, DERYA (My University, 2022)
OBJECTIVE: This study aimed to evaluate the relationship between hospital admission potentially inappropriate medications use (PIM) and in-hospital mortality of COVID-19, considering other possible factors related to mortality. METHODS: The Turkish inappropriate medication use in the elderly (TIME) criteria were used to define PIM. The primary outcome of this study was in-hospital mortality. RESULTS: We included 201 older adults (mean age 73.1±9.4, 48.9% females). The in-hospital mortality rate and prevalence of PIM were 18.9% (n=38) and 96% (n=193), respectively. The most common PIM according to TIME to START was insufficient vitamin D and/or calcium intake per day. Protonpump inhibitor use for multiple drug indications was the most prevalent PIM based on TIME to STOP findings. Mortality was related to PIM in univariate analysis (p=0.005) but not in multivariate analysis (p=0.599). Older age (hazards ratio (HR): 1.08; 95% confidence interval (CI): 1.02–1.13; p=0.005) and higher Nutritional Risk Screening 2002 (NRS-2002) scores were correlated with in-hospital mortality (HR: 1.29; 95%CI 1.00–1.65; p=0.042). CONCLUSION: Mortality was not associated with PIM. Older age and malnutrition were related to in-hospital mortality in COVID-19